Genetic variation of two species with different life‐history traits in the endangered renosterveld of South Africa – a comparative analysis of Eriocephalus africanus and Hemimeris racemosa. (22nd May 2015) - Heelemann, Steffen; Bäuerlein, Veronika; Krug, Cornelia B.; Esler, Karen J.; Poschlod, Peter; Reisch, Christoph
Abstract: We tested the effects of life‐history traits on genetic variation and conducted a comparative analysis of two plant species with differing life‐history traits co‐occurring in the highly endangered renosterveld of South Africa. We selected eighteen renosterveld remnants with varying degrees of size and isolation where populations of the herbaceous, annual and insect‐pollinated Hemimeris racemosa and the shrubby perennial and both wind‐ and insect‐pollinated Eriocephalus africanus occurred. We postulated a lower genetic variation within populations and increased genetic variation between populations in the annual than in the perennial species. Genetic variation was lower within populations of H. racemosa than within E. africanus, as is typical for annual compared to perennial species. Variation within populations was, however, not correlated with fragment size or distance in either of the two species and genetic variation between populations of the two species was comparable ( Φ ST  = 0.10, 0.09).